Redesigning the Azimpur colony: housing complex for government employees Azimpur, Dhaka - Afrin, Tahsin Jawed (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2018.